2002 Cotton Defoliation and Harvest Aid Guide - David L. Wright; Barry J. Brecke (EDIS, 2002)
This document is SS-AGR-181, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published September 2002.